2(3x+7)=5(9-2x)+1

Simple and best practice solution for 2(3x+7)=5(9-2x)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x+7)=5(9-2x)+1 equation:



2(3x+7)=5(9-2x)+1
We move all terms to the left:
2(3x+7)-(5(9-2x)+1)=0
We add all the numbers together, and all the variables
2(3x+7)-(5(-2x+9)+1)=0
We multiply parentheses
6x-(5(-2x+9)+1)+14=0
We calculate terms in parentheses: -(5(-2x+9)+1), so:
5(-2x+9)+1
We multiply parentheses
-10x+45+1
We add all the numbers together, and all the variables
-10x+46
Back to the equation:
-(-10x+46)
We get rid of parentheses
6x+10x-46+14=0
We add all the numbers together, and all the variables
16x-32=0
We move all terms containing x to the left, all other terms to the right
16x=32
x=32/16
x=2

See similar equations:

| .25+12=c | | 3x+7x+9=29 | | x=2/3×2x | | 15x+175=550 | | 1x=2/3×2x | | 2)x+5)=-4 | | 3/4=1-(x/2) | | a=21.8 | | .15x=115000 | | 57+60+x=180 | | 6x-2-11x-9=180 | | 9(x-11)-12=28x-339 | | (2x-5)(8x+9)=0 | | 1/7a-5=2 | | Y=6x+1;(2,3) | | -x-163=12x+24 | | -3(4-y)=y-5+13 | | x+3(x+2)+2x+4)=68 | | 2x+2-3x-5=3+2 | | -7(6+k)=21 | | 4w-4=w+1 | | (x-8)(x+7)=8 | | 4(n+1)=6n+2 | | ²/⁵g=³/5 | | ²/⁵g=³⁵ | | q-12=1= | | 4=(3x+7) | | Y=x+4;(2,4) | | -4t-4=40 | | 5j=7 | | 9j=72 | | 2.8=z-63 |

Equations solver categories